INFLUENCE OF ACCOMMODATION ON FARROWING BEHAVIOUR IN LARGE WHITE YORKSHIRE GILTS (Indian Journal of Animal Production and Management, 2015)
An experiment was conducted to find out the different housing systems on the reproductive behaviour of pigs. Twenty four Large White Yorkshire pigs in the age group of 5 months were selected and randomly divided into four groups consisting of 6 animals each. Among these, two groups were reared under intensive system and two groups under semi intensive system. From each system one group in individual housing and other group in group housing. All pregnant gilts under group housing both from intensive and Semi intensive system of management were transferred to farrowing crate, one week prior to expected date of farrowin,g whereas gilts under individual housing both from intensive and semi-intensive system of management remained in the individual pen itself during farrowing and lactation. Farrowing behaviors were recorded from 3 days prior to farrowing and continued till the placenta was expelled. All the farrowing activities except straw were performed for significantly (P
Keywords: Farrowing behaviour; Housing systems and pigs